Composite Aerogel for Heat Insulation - Oanh T. H. Cao (Chemical Engineering Transactions, 2020)
Silica aerogels are often brittle and MTMS is rather expensive. Therefore, it is necessary to strengthen MTMS silica aerogels and lower their cost. In this research, hydrophobic composite monolithic methyltrimethoxysilane (MTMS) based aerogels were investigated. The aerogels were synthesized by an acid base sol-gel process with solvent exchange and freeze drying. Silica extracted from rice husk ash, poly vinyl alcohol (PVA) and glass wool were combined with MTMS to form the composite aerogels, whose microstructure, thermal property and hydrophobicity were evaluated. The aerogels were found to have thermal conductivity as low as 0.032 W/m.K and water contact angle as high as 152.2°.